Preparando colaboradores para a era digital: habilidades fundamentais para o futuro do trabalho - Ferreira, Naelhy Paiva (Brasil, 2024)
Digital transformation plays a crucial role in reshaping the labor market, requiring organizations and employees to adapt to new technological realities. This study investigates the digital and behavioral skills necessary for adaptation to the Digital Era at Kaizen Company. With an applied and descriptive approach, the research employed semi-structured interviews with seven male employees aged between 30 and 40, all of whom hold higher education degrees. Data analysis was conducted through thematic coding, identifying recurring patterns and themes such as digital literacy, technical skills, emotional intelligence, adaptability, and interpersonal competencies. The results elucidate the essential competencies for digital transformation, also addressing challenges such as resistance to change and stress, as well as the opportunities that automation brings to the organizational environment.